The Cultural Roots of American Islamicism: By Timothy Marr (Cambridge, NY: Cambridge University Press, 2006. 309 pages.) (American Journal of Islam and Society, 2007)
Perceptions of the “other” are a powerful force in day-to-day human interaction,as well as in domestic and international politics. Since the publicationof Edward Said’s Orientalism almost three decades ago, many scholarshave appropriated and debated his thesis about the reality-changing powerof European (and American) discourses on Muslims and Arabs. In the bookunder review, Timothy Marr, professor of English in the American StudiesCurriculum department at the University of North Carolina, Chapel Hill,simultaneously broadens and criticizes Said’s ideas.The Cultural Roots of American Islamicism (a somewhat misleadingtitle for a fascinating book) offers a rich analysis of how Americans appropriatedimages of Islam, Muslim societies, and the Middle East during theseventeenth to nineteenth centuries for various political, social, and cultural– but ultimately American – purposes related to domestic and internationalissues. The author argues that such perceptions, in light of their complex andmultiple uses in American history, are significant because they continue toshape contemporary American approaches to the Muslim world.Marr advances this thesis by looking at an impressive array of historicalsources and documents, as well as secondary literature on various aspects ofAmerican history and culture, in which he finds a multitude of references toIslam and Muslims (or Turks, Saracens etc., respectively). His analysis ofthese references offers a stunning kaleidoscope of American images of theMuslim “other,” but reveals far more about the inner dynamics of Americannation-building and cultural self-definition than about Islam or Muslims ...